A more natural way to construct identity-based identification schemes - YANG, Guomin (Institutional Knowledge at Singapore Management University, 2007)
Constructing identification schemes is one of the fundamental problems in cryptography, and is very useful in practice. An identity-based identification (IBI) scheme allows a prover to identify itself to a public verifier who knows only the claimed identity of the prover and some common information. In this paper, we propose a simple and efficient framework for constructing IBI schemes. Unlike some related framework which constructs IBI schemes from some standard identification schemes, our framework is based on some more fundamental assumptions on intractable problems. Depending on the features of the underlying intractable problems presumed in our framework, we can derive IBI schemes secure against passive, active and concurrent adversaries. We show that the framework can capture a large class of schemes currently proposed, and also has the potential to cover many newly constructed schemes. As an example, based on the Katz-Wang standard signature scheme, we propose a new IBI scheme that is secure against active adversaries in a concurrent manner. It can be seen that our framework also help simplify the security proofs for new IBI schemes. Finally, and of independent interest, we define a new notion for proof systems called Witness Dualism. This notion is weaker than that of witness indistinguishable and we show that it is enough for constructing an IBI scheme secure against the most powerful type of adversaries defined.